PENGARUH IKLIM ORGANISASI DAN GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI - Ramnah Ramnah; Muhammad Harlie; Sulastini Sulastini (Al-KALAM : JURNAL KOMUNIKASI, BISNIS DAN MANAJEMEN, 2017)
Government organizational human resources consisting of leaders and employees. Organization of youth sports culture and tourism is particular agencies a government that has personnel were 60 employees. Organization of youth sports culture and tourism of a system of the indonesian government is a system of government bureaucracy that was overall would be a lot determined by the these agencies.Research aims to understand effects of climate organizations and style leadership of the performance of employees. The kind of research this is research quantitative to test the influence of between variables free variable bound, with the number of respondents about 60 personnel.Research this analyzed by the use of a test statistic spss for windows version 17. The research results show that there are influence in partial between climate organizations and style leadership of the performance of employees. There is the influence of simultaneously between climate organization style leadership of performance.Keywords : organizational climate, leadership style and performance